Doppler Ultrasonography for the Noninvasive Measurement of Uterine Artery Volume Blood Flow Through Gestation in the Pregnant Sheep - Abi Nader, Khalil (2009)
Accurate noninvasive quantification of volume blood flow in the uterine arteries (UtAs) would have clinical and research benefits. We evaluated the correlation and agreement between uterine artery volume blood flow (UtABF) as calculated (cUtABF) from color/pulsed-wave Doppler acquisitions and that measured (mUtABF) by bilateral perivascular transit-time flow probes in 6 pregnant sheep at 2 gestational ages. Out of 22 Doppler acquisitions, 19 were successful. The overall correlation between cUtABF and mUtABF was 0.55 (n ¼ 19, P ¼ .01). Calculated UtABF and mUtABF were significantly correlated in late gestation (n ¼ 11, r ¼ 0.71, P ¼ .01) but not at mid-gestation (n ¼ 8, r ¼ .02, P ¼ .96). By Bland-Altman analysis, the mean cUtABF/mUtABF was 1.15 with 95% limit of agreement (0.26 to 2.56), similar to results previously achieved using power/pulsed-wave Doppler. Despite the acceptable correlation, the limits of agreement between Doppler and transit-time flow probe measurements remain wide. This makes Doppler ultrasonography less than a desirable method to quantify UtABF in studies where accurate quantification is required.